Influence of Aging Time on Asphalt Pavement Performance (Journal of Engineering, 2014)
Aging of asphalt pavements typically occurs through oxidation of the asphalt and evaporation of the lighter maltenes from the binder. The main objective of this study is to evaluate influence of aging on performance of asphalt paving materials.nAsphalt concrete mixtures, were prepared, and subjected to short term aging (STA) procedure which involved heating the loose mixtures in an oven for two aging period of (4 and 8) hours at a temperature of 135 o C. Then it was subject to Long term aging (LTA) procedure using (2 and 5) days aging periods at 85 o C for Marshall compacted specimens. The effect of aging periods on properties of asphalt concrete at optimum asphalt content such as Marshall Properties, indirect tensile strength at 25 o C, Resilient Modulus and resistance to permanent deformation were evaluated. The impact of Short-term and long-term aging on asphalt concrete properties was evaluated. The stiffness of the mixture increases by increasing aging period that lead to increase of Marshall Stability, indirect tensile strength, and the resilient modulus, which leads to increases the resistance of mixtures against permanent deformation. The 8 hr. short term aging causes the Marshall stability, indirect tensile strength at 25 o C and resilient modulus to be increased by 52%, 34 % , 20% respectively as compared with control mixture while, the permanent deformation decreased by (33 %) as compared with control mixture.